Study of distributed coordination function (DCF) and enhanced dcf (EDCF) in IEEE 802.11 MAC protocols for multimedia applications - Chan, C.H (Universiti Malaysia Sarawak, UNIMAS, 2010)
IEEE 802.11e Medium Access Control (MAC) is an enhancement to the legacy IEEE 802.11 standard’s Wireless Local Area Network (WLAN) ideally to support Quality-ofService (QOS). The 802.11e MAC is both centrally-controlled and contention-based channel accesses based. This project covers evaluation of the contention-based channel access mechanism, called Enhanced Distributed Coordination Function (EDCF), in comparison with the 802.11 legacy MAC, Distributed Coordination Function. Three different types of multimedia traffic are considered namely, voice, video and data. The evaluation was performed using ns-2 simulator (version 2.34) on Linux Ubuntu. The metrics used in the evaluation are throughput, delay, jitters and packet loss. The graphs from the metrics benchmarked the performance of EDCF and DCF evaluation. Through this simulation study, EDCF conclusively provides differentiated channel access for various multimedia traffic types. Simulation results proved that comparatively EDCF performs better performance than legacy DCF.